Flame retardants of the future: biobased, organophosphorus, reactive or oligomeric - Howell, Bob A. (Frontiers in Chemistry, 2024)
Polymeric materials have been a great boon to the development and well-being of mankind. However, in the main, these materials are flammable and must be flame retarded for most applications. Many substances have been utilized to impart a measure of flame retardancy.The most widely used and most effective have been organic: organohalogen and organophosphorus compounds. Organohalogen compounds have been popular, low-cost, very effective flame retardants for polymeric materials. However, with the recognition that these compounds readily migrate from a polymer matrix into which they have been incorporated, persist in the environment and pose serious risks to human health, the use of organophosphorus compounds has become prominent. In particular, organophosphorus compounds of appropriate structure derived from readily-available, renewable, low-cost, nontoxic biobased precursors are attractive. Avoidance of the issues of environmental persistence and toxicity associated with organohalogen compounds is possible with these materials. Migration from a polymer matrix may be removed as a deficiency through the use of reactive compounds, i.e., compounds that may be incorporated directly into the polymer structure either by copolymerization or grafting, or oligomeric compounds. Oligomeric materials of branched structure display characteristics of broad compatibility, high effectiveness and lack of migration.